Respons Pertumbuhan Dan Produksi Beberapa Varietas Ubi Jalar (Ipomoea batatas L.) Terhadap Pemberian Kompos Tandan Kosong Kelapa Sawit (TKKS) - Tri Andra Zulkadifta (Jurnal Pertanian Tropik, 2018)
Sweet potato is a staple food for the population group of Indonesia. This research was conducted in Desa Suka Raya, Pancur Batu, Deli Serdang altitude ± 35 m asl from April to August 2017. This research used a factorial randomized block design with two factors. The first factor was varieties with three kinds is Beta 1 ; Lubuk Pakam genotype and Perbaungan genotype and the second factor was application the provision of compost oil palm empty fruit bunches (CEFB) with four kinds without CEFB compost ; CEFB compost 400 g/plant ; CEFB compost 600 g/plant ; CEFB compost 800 g/plant. The results showed that the treatment of the Lubuk Pakam genotype significantly increased the increase of plant length, number of tubers per sample, tuber length per sample, tuber weight per sample and harvest index. Composting CEFB 800 g/plant crops increases the growth of plant length, plant biomass. The interaction between the treatment of varieties with the provision of compost CEFB of Lubuk Pakam genotype with the giving of 800 g /plant had a significant effect on the increase of plant length and tuber weight per sample.